Supraglottic foreign body missed for one month in a child - Sultan Abdul Kader, Mohamed Iliyas; Syafeera, Nadia; Md Nor, Khadijah; Abu bakar, Saraiza; Mat Baki, Marina (Cureus, 2023)
Foreign body (FB) aspiration in children can result in serious complications that can lead to even death. We present a case of a one-year-old girl child with a history of choking one month prior while she was feeding. A bolus of rice was removed at a local clinic. Consequently, within 24 hours, she developed hoarseness and noisy breathing which was treated as an upper respiratory tract infection at two different clinics. This case report aims to highlight the need for otolaryngology consultation in a child with non-resolving respiratory symptoms following episodes of choking. This will prompt an immediate surgical intervention that could prevent potential morbidity and mortality as a result of a compromised airway.